Automatic G1 Parametric Fitting Of Curves And Surfaces To Outlines Of Images - Yahya, Fatimah (2009)
Rapid advancement in imaging technologies produces massive amount of data which can be harnessed for information and knowledge gathering. Mathematical representations of objects of interest from these images are amenable to manipulation of shapes and sizes, thus aiding analysis and design. As a process in reverse engineering, we aim to automatically reproduce a mathematical outline of a 2D contour based image of an object. Next we will reconstruct a 3D object (surface) from its cross-sectional images. It is our objective to have a representation which is reliable, reasonably fast and with flexible accuracy.